Ujawnienie osób uczestniczących w popełnieniu przestępstwa oraz istotnych okoliczności jego popełnienia jako przesłanka obligatoryjnego nadzwyczajnego złagodzenia kary - Gadzińska, Paulina (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The subject of the article is the disclosure of crucial circumstances of committing an offence, which are passed to the law enforcement agencies by the accomplice. The consequence of such disclosure is obligatory mitigation of the penalty. The main issues raised in the article are certain doubts connected with the meaning of dislosure, as well as with the scope, form and moment of disclosure. Additionally, the author describes and analyses the meaning of crucial circumstances of committing an offence and participants in committing an offence.
Keywords: accomplice; offence; crucial circumstances; disclosure; obligatory mitigation; penalty; witness